Synthetic copolymer 1 inhibits human T-cell lines specific for myelin basic protein. - Teitelbaum, D (1992)
Copolymer 1 (Cop 1) is a synthetic basic random copolymer of amino acids that has been shown to be effective in suppression of experimental allergic encephalomyelitis and has been proposed as a candidate drug for multiple sclerosis. Cop 1 is immunologically cross reactive with myelin basic protein (BP) and was shown to inhibit murine BP-specific T-cell lines of various H-2 restrictions. In the present study these findings were extended to include human T-cell lines. Cop 1 competitively inhibited the proliferative responses and interleukin 2 secretion of six BP-specific T-cell lines and 13 clones with several DR restrictions and epitope specificities. Conversely, BP inhibited--albeit to a lesser extent--the response of all the Cop 1-specific T-cell lines and clones, irrespective of their DR restrictions. Another random copolymer of tyrosine, glutamic acid, and alanine, denoted TGA, had no effect on these lines. Neither Cop 1 nor BP inhibited the response of lines and clones specific for purified protein derivative. Cop 1 and BP exerted their cross-inhibitory effects only in the presence of antigen-presenting cells. These results suggest that Cop 1 can compete with BP for the binding to human major histocompatibility complex molecules. In view of recent studies implicating BP reactivity in multiple sclerosis, these findings suggest a possible mechanism for the beneficial effect of Cop 1 in this disease.